Diacerein attenuates vascular dysfunction by reducing inflammatory response and insulin resistance in type 2 diabetic rats - He, An; Shen, Jian; Xue, Yuzhou; Xiang li; Li, Yuanjing; Huang, Longxiang; Lv, Dingyi; Luo, Minghao (Biochemical and biophysical research communications, 2021)
To examine the effect of diacerein on vascular dysfunction in type 2 diabetic rats and elucidate the mechanism of diacerein. In a rat model, type 2 diabetes was induced by high-fat diet and streptozotocin. Vascular function was assessed in vascular reactivity experiment. The effect of diacerein (10 or 20 mg/kg/day) on blood glucose, inflammation and insulin signaling, and modulators in vascular tissue in diabetic rats were investigated by molecular and biochemical approaches. In this study, diacerein inhibited diabetes-induced vascular dysfunction. Diacerein treatment normalized blood glucose, insulin tolerance test, inflammatory cytokine levels and nitric oxide synthases expression in diabetic rats. Moreover, diacerein inhibited NF-κB and NLRP3 pathways and activated insulin signaling pathway related proteins IRS-1 and AKT in diabetic rats. Diacerein improved vascular function effectively in diabetic rats by suppressing inflammation and reducing insulin resistance. These results suggest that diacerein may represent a novel therapy for patients with diabetes. •In our study, we found diacerein inhibited diabetes-induced vascular dysfunction for the first time.•Diacerein treatment normalized blood glucose, insulin resistance, inflammatory cytokine levels and endothelial nitric oxide synthase and inducible nitric oxide synthase expression in diabetic rats.•Diacerein inhibited NF-κB and NLRP3 pathways and activated insulin signaling pathway related proteins IRS-1 and AKT in diabetic rats.